Independence now : the American Revolution, 1763-1783 - Rosen, Daniel (Crossroads America, 2004)
Chronicles the story of the American Revolution and examines British oppression of the colonists, the Boston Tea Party and Boston Massacre, the Battle of Bunker Hill, and the signing of the Declaration of Independence.